(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Metaphors are powerful linguistic and cognitive tools that shape how medical knowledge is communicated and understood. In popular medical writing, they bridge the gap between complex biomedical concepts and everyday experiences. Chronic diseases such as cancer, diabetes, and cardiovascular conditions are often framed through the battle metaphor, which emphasizes struggle and victory. While widely used, this metaphor has been criticized for oversimplifying long-term illness and placing undue responsibility on patients.